Sustainable Strategy toward Community Life Satisfaction in Heritage Tourism - Fitriaty Fitriaty; Shofia Amin; Musnaini Musnaini; Dessy Elliyana; Muhammad Haris Saputra (Ministry of Tourism and Creative Economy/Tourism and Creative Economy Agency Republic of Indonesia, 2024)
This research aims to form a model strategy for community life satisfaction by developing sustainable tourism in cultural heritage sites. This research used mixed method: qualitative method by in-depth interviews with four respondents from local communities, MSMEs, Kawasan Cagar Budaya Nasional (KCBN) Muaro Jambi, government involved in heritage site tourism activities and analyzed using QDA Miner. The quantitative method was by distributing questionnaires using purposive sampling to 200 respondents, and data were processed using SmartPLS to build a holistic model of community life satisfaction in heritage sites. The results of this research are: firstly, social culture and urban landscapes contribute to community satisfaction; secondly, social culture and urban landscape have a significant positive influence on sustainable tourism; thirdly, through sustainable tourism, community life satisfaction will be formed. This research has relevant implications for providing a deeper understanding of the impact of sustainable tourism in improving community life satisfaction in heritage sites by integrating natural values and urban landscape and empowering the local community.